2022
DOI: 10.2147/ijwh.s375675
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Pregnant Women in the Health Management Model of Internet-Based Centering Pregnancy: A Qualitative Study

Abstract: Background CenteringPregnancy Care is a promising group prenatal care innovation that combines assessment, education, and peer support. In China, it is not clear how best to integrate the CenteringPregnancy Care into existing maternal health care models. This qualitative study aimed to explore Chinese pregnant women’s experience in the Internet-based CenteringPregnancy management model. Methods The Internet-based CenteringPregnancy was applied in a tertiary hospital bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Our evidence indicated that in the technical sector, the most challenges related to mothers and providers in countries of both income levels were in the Internet and network connection domain [2,20,36,42,44]. About this issue, other studies confrm the unstable network connection or its coverage problems [1,15,49,54,55,61]. Some participants declared that the Internet was cut of during the virtual visit or in the middle of the consultation, which led to mothers' stress regarding their health and the fetus [2,20,36,44,45].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Our evidence indicated that in the technical sector, the most challenges related to mothers and providers in countries of both income levels were in the Internet and network connection domain [2,20,36,42,44]. About this issue, other studies confrm the unstable network connection or its coverage problems [1,15,49,54,55,61]. Some participants declared that the Internet was cut of during the virtual visit or in the middle of the consultation, which led to mothers' stress regarding their health and the fetus [2,20,36,44,45].…”
Section: Discussionmentioning
confidence: 77%
“…Some studies showed that new and evidence-based information on pregnancy-related topics was made available to mothers through diferent virtual modalities [20,35,[37][38][39]. Other similar studies also confrm this issue [49,54]. However, some mothers from countries with both income levels criticized the low quality of web-based information resources or mobile apps and sometimes did not consider the resources to be reliable [36,[39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Sampling which was then conducted semi-structured interviews to collect qualitative data results in data on empowerment, psychological and social support that can influence the decision-making of pregnant women to be referred to GANC. 3 In conclusion, we agree that GANC can be a new innovation to improve the health of pregnant women in a sustainable manner. 1 However, it is also necessary to consider the geographical conditions between the location of the pregnant woman and also the place where the GANC can be a factor in decision-making.…”
mentioning
confidence: 67%
“…Sampling which was then conducted semi-structured interviews to collect qualitative data results in data on empowerment, psychological and social support that can influence the decision-making of pregnant women to be referred to GANC. 3 …”
Section: Dear Editormentioning
confidence: 99%
“…This approach requires healthcare workers to be trained not only in medical work but also in empathetic communication and emotional support. [7][8][9][10] Given the importance of both clinical skills and humanistic care, this study integrates humanistic care into ET, establishing a novel educational model that combines knowledge, attitude and practice. It aims to provide multidisciplinary offline education for healthcare workers, supported by standardized teaching materials based on a knowledge graph.…”
Section: Introductionmentioning
confidence: 99%